2017
DOI: 10.1039/c7cp01727h
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and intriguing electronic properties of two-dimensional transition metal dichalcogenide alloys

Abstract: Based on the first-principles calculations, we systematically studied the structures and electronic properties of two-dimensional (2D) transition metal dichalcogenide (TMD) alloys with half-to-half mixing of S and Se. Using the chemical potentials of S and Se, the energetic phase diagrams for both single phases and mixed phases of TMD were constructed. A new heterolayer structure (for Sc and Ti) and alternating structure (for Cr, Mn, Fe, Zr, Mo, and W) were proposed for the first time, which were thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Additionally, the structures and electronic properties of 2D TMD alloys with halfto-half mixing of S and Se for Sc, Ti, Cr, Mn, Fe, Zr, Mo and W were studied for the first time. 27 However, currently, a comprehensive study to estimate the transmittance, absorbance, and reflectance (TAR) of 2D materials is very scarce, which is essential for analyzing their efficiency as ultrathin reflectors, transmitters or absorbers. For example, one may think that 2D materials are so thin that they should appear to be essentially transparent with negligible reflection and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the structures and electronic properties of 2D TMD alloys with halfto-half mixing of S and Se for Sc, Ti, Cr, Mn, Fe, Zr, Mo and W were studied for the first time. 27 However, currently, a comprehensive study to estimate the transmittance, absorbance, and reflectance (TAR) of 2D materials is very scarce, which is essential for analyzing their efficiency as ultrathin reflectors, transmitters or absorbers. For example, one may think that 2D materials are so thin that they should appear to be essentially transparent with negligible reflection and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there are two favorable factors for growing alloyed TMC heterojunctions, in contrast to the 3D-structured semiconductors. First, from the point view of thermodynamics, the absence of direct chemical bonding between the alloyed elements favors entropy rather enthalpy-dominated mixing of alloy; , hence, stable and completely mixed alloy can be formed at high temperatures . Second, the exempt requirement on lattice match between TMCs and underlying substrates, because of their weak van der Waals interaction, makes it possible to grow the compositionally distributed and lattice constant spatially varied 2D materials on a single chip.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters used to determine exciton eigenvalues and eigenfunctions as well as the substrate dielectric constants (SiO 2 , hBN) are listed in the table bellow. [66] 4.26 [66] 6.15 [14] 6.12 [67] 3.183 [67] The convergence of the numerical diagonalisation is obtained for first 10 states but we only restrict ourselves to 1s and 2s states. For zero magnetic field Molas et al [68] have shown that the only the first 5 |ns states can be observed.…”
Section: Photoemission Spectrum Of Exciton In Monolayer Mos2mentioning
confidence: 99%